Antecedents of Turnover Intention on the Manufacturing Industry in Banten Province - Sari, Salsabila Rizky Septinia; Nilasari, B. Medina (Archives of Business Research, 2022)
The objective of the empirical study is to analyse the effect of HRM Practices, Work Family Conflict, Supervisor Support on Turnover Intention mediated by Work Engagement. The data used in this study is primary data taken through by distributing questionnaires using purposive sampling method involving 195 respondents in the manufacturing industry in Banten province, Indonesia. The analytical tools in this research is Structural Equation Modeling (SEM) using AMOS version 21. The results of this study are the HRM Practices, Work Family Conflict, Supervisor Support have an influence on Work Engagement and also on Turnover Intention. In the next result, Work Engagement can mediate the effect of HRM Practices on Turnover Intention, Work Family Conflict on Turnover Intention, and Supervisor Support on Turnover Intention. From the results of this study, it is recommended for managers to maintain a low employee turnover rate by increasing employee engagement and encouraging employee growth, so as to achieve effective management performance supported by positive energy and emotional attachment to work.